Digital Resilience Mediation Model on the Influence of Teacher Self-Efficacy and Technostress on Teacher Well-Being - Septyningtyas, Devi Jati; Nai'mah, Tri; Rahman, Mohd Nazri Abdul; Anbari, Mahdi; Silawati, Endah (Universitas Muhammadiyah Surakarta, 2026)
This study was motivated by the increasing demands of digital technology in education, which have the potential to affect teacher well-being, particularly through psychological factors such as teacher self-efficacy, technostress, and digital resilience. This study aims to analyze the influence of teacher self-efficacy and technostress on teacher well-being, as well as to examine the role of digital resilience as a mediator. The study participants consisted of 212 high school teachers recruited using purposive sampling, with the characteristic of being active teachers who use technology in learning. This study used a quantitative approach with a survey method, where data were collected using scales of teacher self-efficacy, technostress, digital resilience, and teacher well-being that had been adapted and tested for validity. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that teacher self-efficacy had a significant effect on digital resilience and teacher well-being, while technostress had a significant effect on teacher well-being. However, digital resilience did not have a significant effect on teacher well-being and did not mediate the relationship between teacher self-efficacy and technostress with teacher well-being. The conclusion of this study confirms that internal factors such as self-confidence play an important role in teacher well-being, while digital adaptation skills do not contribute significantly without the support of a healthy psychological condition and work environment. These findings have important implications for the development of interventions to improve teacher well-being based on strengthening intrapersonal factors in the digital age.